Analisis Rasio Keuangan Terhadap Financial Distress dengan Metode Altman Z-Score - Zulafa Alfina Hilwa; Shinta Permata Sari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Financial distress illustrates the dynamics of a company’s financial condition over time, indicating its capability to sustain performance and solvency while mitigating the risk of bankruptcy during its business operations. This study aims to analyze the effect of financial ratios on Financial Distress in companies within the basic material sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The independent variables used are Return on Assets , Net Profit Margin , Current Ratio, and Total Asset Turnover, while the dependent variable, Financial Distress, is measured using the Altman Z-Score method. This research applies a quantitative approach with secondary data obtained from annual financial reports published on the IDX website. The sample use a purposive sampling technique, resulting in 33 companies or 99 data observations. Data analyze using multinomial logistic regression through SPSS version 27. The results indicate that Net Profit Margin and Current Ratio significantly affect Financial Distress, implying that higher profitability and liquidity reduce the likelihood of financial difficulties. Conversely, Return on Assets and Total Assets Turnover do not affect Financial Distress. Overall, this study highlights the importance of liquidity and profitability management in maintaining corporate financial health and provides valuable insights for investors, management, and policymakers in early detection and prevention of Financial Distress in Indonesia’s strategic industrial sector. Keyword : Financial Distress, Profitability Ratio, Liquidity Ratio, Activity Ratio